Sago and Oil Palm Forests: Local-Global Economic Contestation in Marind-Anim Land, Papua - Akhmad Kadir; Heinzpeter Znoj; Suharno Suharno; Aisyah Ali; Komari Komari (JSW (Jurnal Sosiologi Walisongo), 2022)
The expansion of oil palm plantations has contradictory impacts on traditional communities, such as the Marind-Anim. On the one hand, the operationalization of oil palm plantations provides space for the community to participate in national economic development. On the other hand, oil palm plantations with their various instruments, have forced them to relinquish their customary land. The flow of global economic power through oil palm plantations seems to have dragged a traditional community such as the Marind-Anim to the brink of collapse. This study aims to trace the narrative of oil palm expansion in the Marind-Anim areas and examines the encounter between the indigenous Marind-Anim community and the global economic forces. This study uses a qualitative research method with an ethnographic approach aiming to explore the encounter of the Marind-Anim indigenous community with the global economic forces at the intersection areas. The results show that the function of sago land as an economic foundation is decreasing due to the global economic pressures from the monoculture oil palm plantations because the Marind-Anim indigenous land has become a frontier area for global economic expansion aiming to supply the global food demand. At the same time, the sago plantation as a safety valve for the traditional economy and local food security has been reduced by oil palm plantations.